Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Low-noise balanced homodyne detection with superconducting nanowire single-photon detectors - Protte, Maximilian; Schapeler, Timon; Sperling, Jan; Bartley, Tim (Optica Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) have been widely used to study the discrete nature of quantum states of light in the form of photon-counting experiments. We show that SNSPDs can also be used to study continuous variables of optical quantum states by performing homodyne detection at a bandwidth of 400 kHz. By measuring the interference of a continuous-wave field of a local oscillator with the field of the vacuum state using two SNSPDs, we show that the variance of the difference in count rates is linearly proportional to the photon flux of the local oscillator over almost five orders of magnitude. The resulting shot-noise clearance of (46.0 ± 1.1) dB is the highest reported clearance for a balanced optical homodyne detector, demonstrating their potential for measuring highly squeezed states in the continuous-wave regime. In addition, we measured a CMRR = 22.4 dB. From the joint click counting statistics, we also measure the phase-dependent quadrature of a weak coherent state to demonstrate our device’s functionality as a homodyne detector.

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics

Dispersion control with integrated plasmonic metasurfaces - Geromel, René; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (CLEO: Fundamental Science 2023)
We present a miniaturized pulse shaping device that creates an arbitrary dispersion through the interaction of multiple metasurfaces on less than 2 mm 3 volume. For this, a metalens and a grating-metasurface between two silver mirrors are fabricated. The grating contains further phase information to achieve the device's pulse shaping functionality.

Degenerate photons from a cryogenic spontaneous parametric down-conversion source - Lange, Nina Amelie; Schapeler, Timon; Höpker, Jan Philipp; Protte, Maximilian; Bartley, Tim (Physical Review A)

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Information extraction in photon-counting experiments - Schapeler, Timon; Bartley, Tim (Physical Review A)

A Versatile Metasurface Enabling Superwettability for Self‐Cleaning and Dynamic Color Response - Lu, Jinlong; Sain, Basudeb; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Zentgraf, Thomas (Advanced Optical Materials)
Metasurfaces provide applications for a variety of flat elements and devices due to the ability to modulate light with subwavelength structures. The working principle meanwhile gives rise to the crucial problem and challenge to protect the metasurface from dust or clean the unavoidable contaminants during daily usage. Here, taking advantage of the intelligent bioinspired surfaces which exhibit self-cleaning properties, a versatile dielectric metasurface benefiting from the obtained superhydrophilic or quasi-superhydrophobic states is shown. The design is realized by embedding the metasurface inside a large area of wettability supporting structures, which is highly efficient in fabrication, and achieves both optical and wettability functionality at the same time. The superhydrophilic state enables an enhanced optical response with water, while the quasi-superhydrophobic state imparts the fragile antennas an ability to self-clean dust contamination. Furthermore, the metasurface can be easily switched and repeated between these two wettability or functional states by appropriate treatments in a repeatable way, without degrading the optical performance. The proposed design strategy will bring new opportunities to smart metasurfaces with improved optical performance, versatility, and physical stability.

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (Journal of Physics Communications)

Cryogenic Second-Harmonic Generation in Periodically Poled Lithium Niobate Waveguides - Bartnick, Moritz; Santandrea, Matteo; Höpker, Jan Philipp; Thiele, Frederik; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine; Bartley, Tim (Physical Review Applied)

Quantum detector tomography of a high dynamic-range superconducting nanowire single-photon detector - Schapeler, Timon; Höpker, Jan Philipp; Bartley, Tim (Superconductor Science and Technology)

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

Single-channel electronic readout of a multipixel superconducting nanowire single photon detector - Tiedau, Johannes; Schapeler, Timon; Anant, Vikas; Fedder, Helmut; Silberhorn, Christine; Bartley, Tim (Optics Express)
We present a time-over-threshold readout technique to count the number of activated pixels from an array of superconducting nanowire single photon detectors (SNSPDs). This technique places no additional heatload on the cryostat, and retains the intrinsic count rate of the time-tagger. We demonstrate proof-of-principle operation with respect to a four-pixel device. Furthermore, we show that, given some permissible error threshold, the number of pixels that can be reliably read out scales linearly with the intrinsic signal-to-noise ratio of the individual pixel response.
Keywords: Atomic and Molecular Physics; and Optics

Quantum detector tomography of a 2×2 multi-pixel array of superconducting nanowire single photon detectors - Schapeler, Timon; Höpker, Jan Philipp; Bartley, Tim (Optics Express)

Towards Semiconductor-Superconductor-Crystal Hybrid Integration for Quantum Photonics - Protte, Maximilian; Ebers, Lena; Hammer, Manfred; Höpker, Jan Philipp; Albert, Maximilian; Quiring, Viktor; Meier, Cedrik; Förstner, Jens; Silberhorn, Christine; Bartley, Tim (OSA Quantum 2.0 Conference)
We fabricate silicon tapers to increase the mode overlap of superconducting detectors on Ti:LiNbO3 waveguides. Mode images show a reduction in mode size from 6 µm to 2 µm FWHM, agreeing with beam propagation simulations.
Keywords: tet_topic_waveguide

Cryogenic electro-optic polarisation conversion in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Quiring, Victor; Ricken, Raimund; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Generating two-mode squeezing and Schrödinger cat states with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten
Keywords: pc2-ressources

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Scalability of parametric down-conversion for generating higher-order Fock states - Tiedau, Johannes; Bartley, Tim; Harder, Georg; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review A)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim; Silberhorn, Christine (Optics Express)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review Letters)

Compressive characterization of telecom photon pairs in the spatial and spectral degrees of freedom - Montaut, Nicola; Magaña-Loaiza, Omar S.; Bartley, Tim; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Silberhorn, Christine; Gerrits, Thomas (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Quantum state and mode profile tomography by the overlap - Tiedau, J; Shchesnovich, V S; Mogilevtsev, D; Ansari, V; Harder, G; Bartley, Tim; Korolkova, N; Silberhorn, Christine (New Journal of Physics)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Heralded orthogonalisation of coherent states and their conversion to discrete-variable superpositions - Kruse, Regina; Silberhorn, Christine; Bartley, Tim (Quantum Measurements and Quantum Metrology)
Abstract The nonorthogonality of coherent states is a fundamental property which prevents them from being perfectly and deterministically discriminated. Here, we present an experimentally feasible protocol for the probabilistic orthogonalisation of a pair of coherent states, independent of their amplitude and phase. In contrast to unambiguous state discrimination, a successful operation of our protocol is heralded without measuring the states. As such, they remain suitable for further manipulation and the obtained orthogonal states serve as a discretevariable basis. Therefore, our protocol doubles as a simple continuous-to-discrete variable converter, which may find application in hybrid continuous-discrete quantum information processing protocols.

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, J.; Silberhorn, C.; Vogel, W. (Physical Review Letters)

Towards integrated superconducting detectors on lithium niobate waveguides - Höpker, Jan Philipp; Bartnick, Moritz; Meyer-Scott, Evan; Thiele, Frederik; Meier, Torsten; Bartley, Tim; Krapick, Stephan; Montaut, Nicola M.; Santandrea, Matteo; Herrmann, Harald; Lengeling, Sebastian; Ricken, Raimund; et al. (Quantum Photonic Devices)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Limits of the time-multiplexed photon-counting method - Kruse, Regina; Tiedau, Johannes; Bartley, Tim; Barkhofen, Sonja; Silberhorn, Christine (Physical Review A)

Harnessing temporal modes for multi-photon quantum information processing based on integrated optics - Harder, G.; Ansari, V.; Bartley, Tim; Brecht, Benjamin; Silberhorn, Christine (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In the last few decades, there has been much progress on low loss waveguides, very efficient photon-number detectors and nonlinear processes. Engineered sum-frequency conversion is now at a stage where it allows operation on arbitrary temporal broadband modes, thus making the spectral degree of freedom accessible for information coding. Hereby the information is often encoded into the temporal modes of a single photon. Here, we analyse the prospect of using multi-photon states or squeezed states in different temporal modes based on integrated optics devices. We describe an analogy between mode-selective sum-frequency conversion and a network of spatial beam splitters. Furthermore, we analyse the limits on the achievable squeezing in waveguides with current technology and the loss limits in the conversion process. This article is part of the themed issue ‘Quantum technology for the 21st century’.

Discorrelated quantum states - Meyer-Scott, Evan; Tiedau, Johannes; Harder, Georg; Shalm, Lynden K.; Bartley, Tim (Scientific Reports)

Full statistical mode reconstruction of a light field via a photon-number-resolved measurement - Burenkov, I. A.; Sharma, A. K.; Gerrits, T.; Harder, G.; Bartley, Tim; Silberhorn, Christine; Goldschmidt, E. A.; Polyakov, S. V. (Physical Review A)

Limits on the heralding efficiencies and spectral purities of spectrally filtered single photons from photon-pair sources - Meyer-Scott, Evan; Montaut, Nicola; Tiedau, Johannes; Sansoni, Linda; Herrmann, Harald; Bartley, Tim; Silberhorn, Christine (Physical Review A)

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, Jan; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, J.; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Quantum enhanced estimation of optical detector efficiencies - Barbieri, Marco; Datta, Animesh; Bartley, Tim; Jin, Xian-Min; Kolthammer, W. Steven; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)
Abstract Quantum mechanics establishes the ultimate limit to the scaling of the precision on any parameter, by identifying optimal probe states and measurements. While this paradigm is, at least in principle, adequate for the metrology of quantum channels involving the estimation of phase and loss parameters, we show that estimating the loss parameters associated with a quantum channel and a realistic quantum detector are fundamentally different. While Fock states are provably optimal for the former, we identify a crossover in the nature of the optimal probe state for estimating detector imperfections as a function of the loss parameter using Fisher information as a benchmark. We provide theoretical results for on-off and homodyne detectors, the most widely used detectors in quantum photonics technologies, when using Fock states and coherent states as probes.

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Observing optical coherence across Fock layers with weak-field homodyne detectors - Donati, Gaia; Bartley, Tim; Jin, Xian-Min; Vidrighin, Mihai-Dorian; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Nature Communications)

Direct Observation of Sub-Binomial Light - Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Datta, Animesh; Barbieri, Marco; Walmsley, Ian A. (Physical Review Letters)

Strategies for enhancing quantum entanglement by local photon subtraction - Bartley, Tim; Crowley, Philip J. D.; Datta, Animesh; Nunn, Joshua; Zhang, Lijian; Walmsley, Ian (Physical Review A)

Requirements for two-source entanglement concentration - Vidrighin, Mihai; Bartley, Tim; Donati, Gaia; Jin, Xian-Min; Barbieri, Marco; Kolthammer, W. Steven; Datta, Animesh; Walmsley, Ian A. (Quantum Measurements and Quantum Metrology)

Multiphoton state engineering by heralded interference between single photons and coherent states - Bartley, Tim; Donati, Gaia; Spring, Justin B.; Jin, Xian-Min; Barbieri, Marco; Datta, Animesh; Smith, Brian J.; Walmsley, Ian A. (Physical Review A)

Continuous phase stabilization and active interferometer control using two modes - Jotzu, Gregor; Bartley, Tim; Coldenstrodt-Ronge, Hendrik B.; Smith, Brian J.; Walmsley, Ian A. (Journal of Modern Optics)

Feasibility of free space quantum key distribution with coherent polarization states - Elser, D.; Bartley, Tim; Heim, B.; Wittmann, Ch; Sych, D.; Leuchs, G. (New Journal of Physics)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100 m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation.

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, B.; Elser, D.; Bartley, Tim; Sabuncu, M.; Wittmann, C.; Sych, D.; Marquardt, C.; Leuchs, G. (Applied Physics B)